Percorrendo os caminhos da inclusão digital: o Projeto Um computador por aluno - UCA em São João da Ponta (PA) - Pereira, Tânia Elizette Barata (2013)
New information and communication technologies have given rise to modifications in modern social relations, with the arrival of the “information society”. In this context the One Computador per Student - UCA project has been initiated to promote digital inclusion and to bring Brazil into the information society. This research treats the implementation of the UCA project in the rural municipality of São João da Ponta in the northern Brazilian state of Pará, examining the promotion of digital inclusion among students. Ethnographic field research was undertaken in order to describe the UCA project in terms of local culture and conditions. The notion of socio-digital inclusion was central to this research (WARSCHAUER, 2006; BECKER, 2009; CYSNE 2007; DEMO, 2005; SORJ, 2003). Results indicate that the UCA Project promoted digital inclusion, did not modify the physical structure of participating schools nor took over their spaces. The project promoted digital literacy and community development (WARCHAUER, 2006). The UCA Project obtained its economic and social objectives, but not its educational goals of improving educational quality by immersion of both students and teachers in digital culture. On the other hand, the project opened up new educational opportunities for current and former students and their families in various places in the municipality. Considering the expected educational, social and transformational possibilities of the project, both within schools and communities, a timid but nevertheless evident promotion of socio-digital inclusion was found among project participants.